What is it going to cost? Empirical evidence from a systematic literature review of audit fee determinants - Markus Widmann; Florian Follert; Matthias Wolz (Management Review Quarterly, 2020)
The audit market is subject to ongoing regulation to ensure or improve the quality of audit services. For this reason, international research on the audit market is highly popular. As part of this discussion, pricing is considered one of the most relevant aspects of audits. However, a remarkable heterogeneity of the control variables used in empirical studies can be observed. Prior meta-analyses on audit fees already summarized and categorized them for audit fee studies covering financial periods until fiscal year 2007. We contribute to the international literature with an up-to date and systematic review approach on audit fee studies published in international relevant scientific journals (JQ3 A0.167em+0.167em, A, B). In addition to prior reviews and meta-analyses, we finally suggest a standard model for the most important fee drivers that can be used for future audit fee studies. Our unique approach is based on an EBSCO keyword search with a sample of 385 papers published in international relevant scientific journals (JQ3 A0.167em+0.167em, A, B) and is using a scoring model to assess significance of audit fee control variables. On the one hand, we enrich the literature by a new state of the art paper on pricing within audit firms. On the other hand, we contribute to the international literature on audit markets from a theoretical point of view by deriving a new testable model of audit fee determinants. Therefore, our empirical results provide several fundamental insights that can be used for further empirical and theoretical research on the pricing of audit services. Thus, the results are meaningful not only for researchers within the field of auditing but also for experts in management, pricing or European legislature.
Keywords: D43; M42; M48; 650; Audit fees; Audit pricing; Auditing; Auditor tenure